MANAGING CHILD-FRIENDLY SCHOOL PROGRAMS THROUGH INNOVATIVE PRINCIPALS LEADERSHIP: EVIDENCE FROM SD NEGERI BEJI 1 - Kurnia Nur Permata Aisah; Widya Kusumaningsih; Nurkolis Nurkolis (SOSIOEDUKASI, 2026)
This study aims to analyze the innovative leadership strategies of school principals in managing the Child-Friendly School (CFS) program at SD Negeri Beji 1. The study employed a qualitative approach using a case study design. The research subjects included the principal, teachers, educational staff, students, parents, school committee members, and supervisors, who were selected purposively. Data were collected through in-depth interviews, observations, and documentation, and analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. Data validity was ensured through source, technique, and time triangulation, as well as member checking. The findings reveal that the principal’s innovative leadership strategies were implemented through the integration of management functions, including participatory and needs-based planning, collaborative organizing, program implementation oriented toward child-friendly principles, and continuous supervision. Innovative leadership was found to be a key factor in creating a safe, comfortable, and supportive learning environment that fosters students’ holistic development. This study contributes to the development of an innovative leadership model based on school management within the context of Child-Friendly Schools.